In heaven as it is on earth: Joseph Smith and the early Mormon conquest of death - Brown, Samuel Morris (Oxford University Press, 2012)
"Melancholly reflections" : Joseph Smith and holy dying -- The corpse and its rest -- Relics, graves, and the treasure quest -- Hallowed ground : tombs, Indians, and Eden -- Seerhood, pure language, and the silence of the grave -- The new and everlasting covenant -- Negotiating death and afterlife in Nauvoo -- The "lineage of my preasthood" and the chain of belonging -- Divine anthropology : translating the suprahuman chain -- "Death cannot conquer the hero again" : the death and afterlife of a martyr